Power production and microbial community composition in thermophilic acetate-fed up-flow and flow-through microbial fuel cells. (December 2019) - Dessì, Paolo; Chatterjee, Pritha; Mills, Simon; Kokko, Marika; Lakaniemi, Aino-Maija; Collins, Gavin; Lens, Piet N.L.
Graphical abstract: Highlights: An up-flow and a flow-through MFC were operated at 55 °C for the first time. Planktonic community from up-flow MFC can be used as inoculum for fast MFC start-up. Changing MFC configuration caused a shift from Tepidiphilus to Ureibacillus. MFC performance was similar despite the different MFC type and prevalent organism. Abstract: The microbial communities developed from a mixed-species culture in up-flow and flow-through configurations of thermophilic (55 °C) microbial fuel cells (MFCs), and their power production from acetate, were investigated. The up-flow MFC was operated for 202 days, obtaining an average power density of 0.13 W/m 3, and Tepidiphilus was the dominant transcriptionally-active microorganisms. The planktonic community developed in the up-flow MFC was used to inoculate a flow-through MFC resulting in the proliferation of Ureibacillus, whose relative abundance increased from 1 to 61% after 45 days. Despite the differences between the up-flow and flow-through MFCs, including the anode electrode, hydrodynamic conditions, and the predominant microorganism, similar (p = 0.05) volumetric power (0.11–0.13 W/m 3 ), coulombic efficiency (16–18%) and acetate consumption rates (55–69 mg/L/d) were obtained from both. This suggests that though MFC design can shape the active component of the thermophilic microbial community, the consortia are resilient and can maintain similar performance in different MFC configurations.